Continuous Activity Assay for HDAC11 Enabling Reevaluation of HDAC Inhibitors - Kutil, Zsófia; Mikešová, Jana; Zessin, Matthes; Meleshin, Marat; Nováková, Zora; Alquicer, Glenda; Kozikowski, Alan; Sippl, Wolfgang; Bařinka, Cyril; Schutkowski, Mike (ACS omega, 2019)
Histone deacetylase 11 (HDAC11) preferentially removes fatty acid residues from lysine side chains in a peptide or protein environment. Here, we report the development and validation of a continuous fluorescence-based activity assay using an internally quenched TNFα-derived peptide derivative as a substrate. The threonine residue in the +1 position was replaced by the quencher amino acid 3'-nitro-l-tyrosine and the fatty acyl moiety substituted by 2-aminobenzoylated 11-aminoundecanoic acid. The resulting peptide substrate enables fluorescence-based direct and continuous readout of HDAC11-mediated amide bond cleavage fully compatible with high-throughput screening formats. The Z'-factor is higher than 0.85 for the 15 μM substrate concentration, and the signal-to-noise ratio exceeds 150 for 384-well plates. In the absence of NAD+, this substrate is specific for HDAC11. Reevaluation of inhibitory data using our novel assay revealed limited potency and selectivity of known HDAC inhibitors, including Elevenostat, a putative HDAC11-specific inhibitor.